Phenolic Compounds from the Leaves of Castanopsis fargesii - Huang, Yong-Lin (Molecules, 2017)
In the course of a phytochemical and chemotaxonomical investigation of Castanopsis species (Fagaceae), three new phenolic compounds, (3R,1′S)-[1′-(6″-O-galloyl-β-d-gluco-pyranosyl)oxyethyl]-3-hydroxy-dihydrofuran-2(3H)-one (1), (2R,3S)-2-[2′-(galloyl)oxyethyl]-dihydroxybutanoic acid (2), and (3S,4S)-3-hydroxymethyl-3,4-dihydro-5,6,7-trihydroxy-4-(4′-hydroxy-3′-methoxyphenyl)-1H-[2]-benzopyran-1-one (3) were isolated from the fresh leaves of Castanopsis fargesii. In addition, a known phenolic glycoside, gentisic acid 5-O-α-l-rhamnopyranosyl-(1→2)-β-d-glucopyranoside (4) was also isolated and identified. Their structures were elucidated by means of spectroscopic methods including one- and two-dimensional NMR techniques.